Imaging the Nonlinear Plasmoemission Dynamics of Electrons from Strong Plasmonic Fields - Podbiel, Daniel; Kahl, Philip; Makris, Andreas; Frank, Bettina; Sindermann, Simon; Davis, Timothy J; Giessen, Harald; Hoegen, Michael Horn-von; Meyer zu Heringdorf, Frank-J (Nano letters, 2017)
We use subcycle time-resolved photoemission microscopy to unambiguously distinguish optically triggered electron emission (photoemission) from effects caused purely by the plasmonic field (termed “plasmoemission”). We find from time-resolved imaging that nonlinear plasmoemission is dominated by the transverse plasmon field component by utilizing a transient standing wave from two counter-propagating plasmon pulses of opposite transverse spin. From plasmonic foci on flat metal surfaces, we observe highly nonlinear plasmoemission up to the fifth power of intensity and quantized energy transfer, which reflects the quantum-mechanical nature of surface plasmons. Our work constitutes the basis for novel plasmonic devices such as nanometer-confined ultrafast electron sources as well as applications in time-resolved electron microscopy.